Paraneoplastic syndromes in childhood neuroblastoma - Małek, Natalia; Emerla, Sara; Brożyna, Aleksandra; Kwiatkowska, Anita; Bydliński, Arkadiusz; Karłowicz, Konrad; Hermanowska, Maria; Lubomirska, Julia; Figurowska, Patrycja; Ciulkiewicz, Łukasz; et al. (Journal of Education, Health and Sport, 2024)
INTRODUCTION: Neuroblastoma is a malignant tumor primarily affecting infants. Originating from embryonic cells of the sympathetic nervous system, NB commonly arises in the adrenal glands, followed by the abdomen, mediastinum, head, and neck. Clinical presentation varies depending on the tumor’s location. General symptoms, if present, include fatigue, weight loss, and fever. The paraneoplastic syndrome refers to symptoms and disorders associated with malignant tumors but not directly caused by the tumor itself or its metastases. Opsoclonus-myoclonus syndrome and diarrhea are the most common paraneoplastic syndromes linked to neuroblastoma. REVIEW METHODS: The article was conducted using PubMed and Google Scholar data concerning paraneoplastic syndromes associated with neuroblastoma. THE STATE OF KNOWLEDGE: Opsoclonus-myoclonus syndrome is a neurological paraneoplastic syndrome that presents itself with characteristic eye movement disorder, short, involuntary, irregular twitches or spasms occurring in a muscle, sleep disturbance, and changes in behavior. Diarrhea resulting in hypokalemia may be also present as a paraneoplastic syndrome associated with neuroblastoma. Cushing’s syndrome is a rare condition in childhood, but it also may be linked to neuroblastoma. CONCLUSIONS: Neuroblastoma is one of the most common childhood cancers, Paraneoplastic syndromes associated with neuroblastoma are rare conditions. Diagnosing chronic diarrhea, OMS, and Cushing’s syndrome should always lead to the exclusion of neuroblastoma. Heightened awareness among pediatricians regarding PNS could result in faster diagnosis, timely treatment commencement, and ultimately enhance patient prognosis.